Solvability of a Quadratic Integral Equation of Fredholm Type with Supremum in Hölder Spaces. (29th April 2014) - Caballero Mena, J.; Nalepa, R.; Sadarangani, K.
Abstract : Using the classical Schauder fixed point theorem, we prove the existence of solutions of a quadratic integral equation of Fredholm type with supremum in the space of functions satisfying the Hölder condition.